Influence of the Properties of Surface Polyoxide Structures on Wear Processes in Solid Bodies; Inorganic Materials: Applied Research; Vol. 11, iss. 4 - Nesterenko V. P. Vladimir Petrovich; Kononova A. A. Anastasiya Aleksandrovna; Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich; Kondratyuk А. А. Alexey Alekseevich; Botvalinskaya A. A. Anastasiya Aleksandrovna; Galanov Yu. I. Yury Ivanovich (2020, 2020)
Title screen